(3eUMMGJ CadGWhfs - (3eMeO GdPGcQs
(3ChdgG (B:s
(3HYO gPG GdHMK GdChd Yf WQjb eRGLgG HCf jMJGL gd Jchf ZHjWI HMGdgG ceG gi HYO Cf JNQL ef eYGOfgG ChdkG s
(3BNQgG (B:s
(3hefgG eG fXehG ef GdCYeGd hbO TQMJg hCJjJ Yfg HZjQ WdH s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs